Cows' milk exclusion diet during infancy: Is there a long‐term effect on children's eating behaviour and food preferences?. Issue 2 (21st January 2016) - Maslin, Kate; Grundy, Jane; Glasbey, Gillian; Dean, Tara; Arshad, Syed Hasan; Grimshaw, Kate; Oliver, Erin; Roberts, Graham; Venter, Carina
Abstract: Background: Dietary restriction during infancy may influence later eating behaviour. The aim of this study was to determine whether consuming a cows' milk exclusion (CME) diet during infancy affects eating habits in later childhood, once cows' milk has been reintroduced into the diet. Methods: Children were recruited from two large birth cohort studies in the UK. A small number of participants were recruited from allergy clinic. Two groups were recruited: an experimental group of children who had consumed a CME diet during infancy and a control group, who had consumed an unrestricted diet during infancy. Parents and children completed questionnaires regarding eating behaviour and food preferences. Results: In total, 101 children of mean age 11.5 years were recruited (28 CME and 73 controls). The CME group scored significantly higher on 'slowness of eating' and on the combined 'avoidant eating behaviour' construct (p < 0.01). The number of foods avoided and symptoms was associated with higher levels of avoidant eating behaviour (p < 0.05). The CME group rated liking for several dairy foods (butter, cream, chocolate, full fat milk and ice cream) significantly lower than the control group (p < 0.05), although there were no significant differences seen for any other category of food. Conclusion: This study demonstrated that consuming a CME diet during infancy has persistent and long‐term effects on eating habits and food preferences. To reduce future negative eating behaviours, children's exclusion diets need to be as varied as possible and reintroduction of cows' milk products closely monitored. Abstract :